Mechanistic Exploration of Moringa oleifera Leaf Bioactives in Prostate Cancer Using Network Pharmacology - Tengke, Feniea Wulan Agaype; Tallei, Trina Ekawati; Turalaki, Grace Lendawati Amelia; Tendean, Lydia Estelina Naomi; Kaseke, Martha Marie; Niode, Nurdjannah Jane; Fatimawali, Fatimawali (Grimsa Journal of Science Engineering and Technology, 2026)
Prostate cancer remains one of the most prevalent malignancies in men worldwide, while current therapeutic strategies are often associated with adverse effects and the emergence of drug resistance, highlighting the need for safer and more effective alternatives. This study aimed to elucidate the multitarget molecular mechanisms of bioactive compounds derived from Moringa oleifera leaves against prostate cancer using an integrated in silico network pharmacology approach. A total of 137 bioactive compounds were collected from LC–MS/MS profiling data and phytochemical databases, of which 20 compounds with high predicted biological activity were prioritized based on Way2Drug PASS analysis. Potential protein targets were predicted and intersected with prostate cancer–associated genes to identify shared targets. Protein–protein interaction network analysis revealed 536 overlapping targets, with ten hub proteins, ESR1, AKT1, SRC, EGFR, TP53, HSP90AA1, PIK3CA, HSP90AB1, PIK3R1, and MAPK1, identified as central nodes. Pathway enrichment analysis demonstrated that these targets were predominantly involved in cancer-related signaling pathways, including pathways associated with EGFR tyrosine kinase inhibitor resistance. Pharmacokinetic and toxicity assessments indicated that several compounds, such as isorhamnetin, kaempferol, tocopherol, and afzelin, exhibited favorable drug-likeness properties and low predicted toxicity. Overall, these findings suggest that bioactive compounds from Moringa oleifera leaves exert anticancer effects through a multitarget and multi pathway mode of action rather than single-protein modulation. This study provides systematic insight into the molecular mechanisms underlying the anti–prostate cancer potential of Moringa oleifera leaves and supports their relevance as candidates for further experimental validation and drug development.